Inequalities in the burden of female breast cancer in Brazil, 1990-2017 - Maximiliano Ribeiro Guerra; Mário Círio Nogueira; Deborah Carvalho Malta; Camila Soares Lima Côrrea; Maria de Fatima Marinho de Souza; Maria Paula Curado; Mariana Santos Felisbino-Mendes; Meghan Mooney; Mohsen Naghavi; Maria Teresa Bustamante-Teixeira (BMC, 2020)
Abstract Background Breast cancer is the most frequently diagnosed cancer in women and the leading cause of cancer death among females worldwide. In recent decades, breast cancer death rates have been stable or decreasing in more developed regions; however, this has not been observed in less developed regions. This study aims to evaluate inequalities in the burden of female breast cancer in Brazil including an analysis of interregional and interstate patterns in incidence, mortality and disability-adjusted life years (DALYs) rates from 1990 to 2017, and mortality-to-incidence ratio (MIR), and their association with the Socio-demographic Index (SDI). Methods Using estimates from the global burden of disease (GBD) study, we applied a spatial exploratory analysis technique to obtain measurements of global and local spatial correlation. Percentage changes of breast cancer incidence, mortality, and DALYs rates between 1990 and 2017 were calculated, and maps were developed to show the spatial distribution of the variables. Spatial panel models were adjusted to investigate the association between rates and SDI in Brazilian states. Results In Brazil, while breast cancer mortality rate have had modest reduction (−4.45%; 95% UI: −6.97; −1.76) between 1990 and 2017, the incidence rate increased substantially (+39.99%; 95% UI: 34.90; 45.39). Breast cancer incidence and mortality rates in 1990 and 2017 were higher in regions with higher SDI, i.e., the most developed ones. While SDI increased in all Brazilian states between 1990 and 2017, notably in less developed regions, MIR decreased, more notably in more developed regions. The SDI had a positive association with incidence rate and a negative association with MIR. Conclusion Such findings suggest an improvement in breast cancer survival in the period, which may be related to a broader access to diagnostic methods and treatment. This study also revealed the inequality in breast cancer outcomes among Brazilian states and may guide public policy priorities for disease control in the country.